The effectiveness of pre-contoured titanium alloy rods in inducing thoracic kyphosis after sequential spinal releases in an in vitro biomechanical model - Shi, Jinhui; Ordway, Nathaniel R.; Sun, Mike H.; Albanese, Stephen A.; Lavelle, William F. (Frontiers in Surgery, 2023)
cadaveric spines and determine the effectiveness of sequential surgical AIS release procedures. Methods: Six thoracolumbar (T3-L2) spine specimens were instrumented with pedicle screws bilaterally (T4-T12). Over correction using pre-contoured rods was performed for intact condition and Cobb angle was measured. Rod radius of curvature (RoC) was measured pre- and post-reduction. The process was repeated following sequential release procedures of 1) interspinous and supraspinous ligaments (ISL); 2) ligamentum flavum; 3) Ponte osteotomy; 4) posterior longitudinal ligament (PLL); and 5) transforaminal discectomy. Cobb measurements determined the effective contribution of release on TK and RoC data displayed effects of reduction to the rods. Results: The intact TK(T4-12) was 38.0° and increased to 51.7° with rod reduction and over correction. Each release resulted in 5°-7°of additional kyphosis; the largest releases were ISL and PLL. All releases resulted in significant increases in kyphosis compared to intact with rod reduction and over correction. Regionally, kyphosis increased 2°for each region following successive releases. Comparing RoC before and after reduction showed significant 6° loss in rod curvature independent of release type. Conclusion: Kyphosis increased in the thoracic spine using pre-contoured and over corrected rods. Subsequent posterior releases provided a substantial, meaningful clinical change in the ability to induce additional kyphosis. Regardless of the number of releases, the ability of the rods to induce and over correct kyphosis was reduced following reduction.